2018
DOI: 10.3866/pku.whxb201802051
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Deformation Potential, Electron-Phonon Coupling, and Carrier Transports of Layered Systems

Abstract: The electronic structures, deformation potential, electron-phonon couplings (EPCs), and intrinsic charge transport of layered systemsthe sp + sp 2 hybridized carbon allotropes, graphynes (GYs) and graphdiynes (GDYs), as well as sp 2 + sp 3 hybridized structure with buckling, such as staninehave been investigated theoretically. Computational studies showed that, similar to graphene, some GYs can possess Dirac cones (such as α-, β-, and 6,6,12-GYs), and that the electronic properties of GYs and GDYs can be tuned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Generally speaking, hydrogenation dramatically reduces the mobility of graphene. The theoretical mobility of graphene (3.2 × 10 5 cm 2 /(V s)[ 28 ]) is several orders of magnitude higher than that of HG. In addition, HGs have asymmetric (μ e ≠ μ h ) and anisotropic ( μ (ΓM) ≠ μ (ΓK)) mobilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, hydrogenation dramatically reduces the mobility of graphene. The theoretical mobility of graphene (3.2 × 10 5 cm 2 /(V s)[ 28 ]) is several orders of magnitude higher than that of HG. In addition, HGs have asymmetric (μ e ≠ μ h ) and anisotropic ( μ (ΓM) ≠ μ (ΓK)) mobilities.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that the DPA method may overestimate the mobilities of arsenene, antimonene [ 26 ], and silicene [ 27 ] because it does not consider the effect of flexural acoustic (ZA) phonons. Shuai et al [ 28 , 29 ] discussed the applicability of DPA and found that it can estimate the electronic properties of graphene and graphyne well. The ZA phonons play a minor role in electron-phonon interactions for two-dimensional carbon materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has relatively many carbon chemical bonds, a great conjugated system, and prominent chemical properties. In addition, GDY has great potential in the field of electronics and energy 35,47,[157][158][159][160][161][162][163][164][165][166][167][168] . In summary, GDR materials are excellent catalyst, energy and sensor materials.…”
Section: Application Of Gdy In Catalysismentioning
confidence: 99%
“…Based on the discovery of graphene, two-dimensional (2D) carbon allotropes have attracted wide attention, especially 2D graphyne [18][19][20][21][22] . Unlike graphene, graphyne has both sp and sp 2 hybrid carbon bonds 23,24 . The sp hybrid carbon bonds destroy the original honeycomb lattice of graphene, resulting in four different geometries of graphyne: α-graphyne, β-graphyne, γgraphyne and 6,6,12-graphyne 25,26 .…”
mentioning
confidence: 99%